Le gouvernement sécuritaire palestinien au prisme de l’émeute - Minas Ouchaklian (Revue des Mondes Musulmans et de la Méditerranée, 2020)
Since 2007, the role of the security apparatus in the Palestinian Authority's (PA) management of populations under its control has increased significantly. Through the report of a field survey conducted in 2017 in the Dheisheh refugee camp, this article examines how Palestinian security policy affects relations between subordinate classes in the West Bank and central and local government. This survey was conducted in 2017 following related clashes between camp youth and security forces. In the wake of these events, the Palestinian security services made arrests which camp youth protested by repeatedly blocking the road along Dheisheh. The article discusses how Palestinian authority and grassroots activists respond to these events, and questions how these are spoken of, and often ignored, by camp residents. It shows how, within the framework of a protest mobilization, the security logic promoted by the PA is internalized by the actors.